THE RELATIONSHIP BETWEEN FEAR OF MISSING OUT AND QUARTER LIFE CRISIS WITH PROCRASTINATION IN PRIVATE UNIVERSITY STUDENTS IN SIDOARJO - Giasus, Rayhan Ravadhan; Laili, Nurfi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: Education is long life or all the time. Education in Indonesian is divided into several levels from elementary, secondary, to tertiary levels. In Indonesia, education is under the Ministry of Education, Culture, Research and Technology. College is a stage for someone who wants to earn a bachelor’s degree. However, some students who have entered the final semester still have not completed their studies. Of course, there are things behind the student. Procrastination is something that students experience. From this, procrastination becomes the focus of this research. Method: The research employs a quantitative method with an axial sampling technique. The population in this study is all students of private universities in Sidoarjo, and the analysis technique uses Pearson correlation. Results: The result of β = 0.473 variables of fear of missing out (X1) and β = 0.649 variables of quarter life crisis against procrastination were obtained, indicating a positive relationship between variables X1 and X2 to variable Y. Novelty: This research provides new insights by examining the influence of fear of missing out and quarter life crisis on procrastination among final semester students in private universities, a focus that has not been extensively explored in previous studies.